Discovery of Novel Prognostic Biomarkers and Therapeutic Targets for Esophageal Cancer - Zhao, Qian; Qiu, Yuyu; Yang, Jinghua; Yang, Zhong-Fa (Archives of Clinical and Biomedical Research, 2020)
Esophageal cancer is one of the most common and lethal malignant tumors. Previous studies revealed the importance of microRNA (miRNA) and their targets in the occurrence, metastasis and prognosis of esophageal cancer. With the availability of The Cancer Genome Atlas (TCGA) database and the development of analytical tools, it is efficient and convenient to identify new biomarkers and key target genes associated with esophageal cancer prognosis through bioinformatic data mining. Five differentially expressed microRNA genes were identified to have significant association with the survival of the esophageal patients. Seven differentially expressed mRNA targets were selected to have significant association with the poor outcomes. These microRNA and mRNA genes could be the candidate biomarkers for tumor prognosis and/or therapeutic targets to improve the survival of esophageal cancer patients.